Mercury Contamination in Selected Edible Plants and Soil from Artisanal and Small-scale Gold Mining in Sukabumi Regency, Indonesia - Saragih, Grace Serepina; Tapriziah, Ely Rahmi; Syofyan, Yunesfi; Masitoh, Siti; Pandiangan, Yohana Sari Hotmatua; Andriantoro, Andriantoro (UI Scholars Hub, 2021)
Artisanal and small-scale gold mining (ASGM) activities often pollute soil, water, and air, thereby achieving widespread proliferation, and contaminating the surrounding biota including plants. Mercury contamination on agricultural land around ASGM areas has been widely reported. This study aims to determine the total mercury contamination in plants and soil around active ASGM sites in Sukabumi Regency, Indonesia, namely, Waluran, Lengkong, and Ciemas Districts. Total mercury (Hg) content was measured from 27 plant samples (including cassava [Manihot utilisima], rice [Oryza sativa], and papaya [Carica papaya]), 7 rhizosphere soil samples, and 7 non-rhizosphere soil samples. Data were analyzed using Kruskal–Wallis test. Results showed no significant difference in total mercury concentrations among locations or plant parts, between rhizosphere and non-rhizosphere soils (p > 0.05), and among cassava plant parts, papaya, and rice. The highest mercury level was found in cassava (0.33–43.27 ppm). Mercury contamination in rice and papaya was relatively low at 0.03–1.22 and 0.06–5.11 ppm, respectively. According to the Regulation of the Head of BPOM of the Republic of Indonesia Number 23 of 2017 concerning the Maximum Limit of Heavy Metal Contamination in Processed Food, 0.03 ppm is the maximum limit of mercury contamination in fruits, vegetables, and cereals. Therefore, all plant samples around the ASGM sites have exceeded the maximum mercury contamination and thus are not suitable for consumption.